2014
DOI: 10.1111/hsc.12111
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed community services for older Australians: a stepped capacity-building approach

Abstract: Consumer-directed care (CDC) is increasingly widespread among aged care service options in Organisation for Economic Co-operation and Development (OECD) countries. However, the evidence base regarding the programmatic and contextual factors that affect the outcome of CDC interventions is surprisingly small. This paper reports on a self-directed care approach for older Australians with complex care needs. A multi-methods longitudinal comparative cohort study was employed comprising 4 survey tools and 56 semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…This limited understanding left older people feeling confused, to the point where many simply continued to rely on traditional home‐care or day‐care services, as opposed to actively choosing their care arrangements (Norrie et al, , p. 182). Ottmann and Mohebbi () similarly note that in their multimethods longitudinal comparative cohort study of DF interventions in Australia, the most important barrier to uptake was “a lack of perceived knowledge, authority, and expertise” (p. 607). Thus, knowledge limitations appear to impact clients’ experience of DF at both early and later stages of DF use.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This limited understanding left older people feeling confused, to the point where many simply continued to rely on traditional home‐care or day‐care services, as opposed to actively choosing their care arrangements (Norrie et al, , p. 182). Ottmann and Mohebbi () similarly note that in their multimethods longitudinal comparative cohort study of DF interventions in Australia, the most important barrier to uptake was “a lack of perceived knowledge, authority, and expertise” (p. 607). Thus, knowledge limitations appear to impact clients’ experience of DF at both early and later stages of DF use.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The literature indicates that a far larger number of clients are interested in self‐directing aspects of their care, like choosing their care‐givers and the care schedule. For instance, Ottmann and Mohebbi () report that “it appears that older Australian's preferences regarding self‐direction are only in a very limited sense motivated by a voucher/cash option and greater financial and administrative control and responsibility. [Instead] a far larger number of clients were interested in self‐directing aspects of their care, resulting in greater decisional authority and better and more direct access to services” (p. 609).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from previous research has shown increased levels of uptake and satisfaction with CDC models of service delivery, especially among younger age groups . The availability of information/knowledge about CDC has been highlighted as a key facilitator to uptake of the model . It was hypothesized that individuals receiving CDC services were therefore more likely to be younger and have some prior knowledge of CDC.…”
Section: Methodsmentioning
confidence: 99%
“…14,16 The availability of information/knowledge about CDC has been highlighted as a key facilitator to uptake of the model. 21 It was hypothesized that individuals receiving CDC services were therefore more likely to be younger and have some prior knowledge of CDC. It was also hypothesized that individuals receiving CDC services would have a better quality of life (as measured by both the EQ-5D-5 L and ICECAP-O) compared with those receiving traditional PDC services.…”
Section: Methodsmentioning
confidence: 99%